Haemagglutinating activity of canine parvovirus - KUMAR, PRAVEEN; GARG, S K; BANDYOPADHYAY, S K; SINGH, RASHMI; SHRIVASTAVA, SAMEER (The Indian Journal of Animal Sciences, 2014)
Haemagglutination is an important characteristic of non-defective parvovirus. The HA test is simple, convenient and comparatively more accurate. The present study was aimed to standardize the HA test using erythrocytes of different species, and to analyze the effect of different incubation temperatures, buffers and pH on the HA reaction. The porcine erythrocytes when used at an incubation temperature of 4oC gave best results. Highest HA titer was obtained using PBS, PBSS and PBS with 0.1 % BSA as diluent in the pH range of 4-6. Also its specificity was ascertained by haemagglutination inhibition test and a HI titer of 3120 was obtained. Using the standardized reagents, HA test was used to detect CPV in the fecal samples from clinical cases and experimentally infected pup.